2008
DOI: 10.1016/j.adolescence.2008.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Why embarrassment inhibits the acquisition and use of condoms: A qualitative approach to understanding risky sexual behaviour

Abstract: This article is based on research commissioned by the UK Government's Teenage Pregnancy Unit. The Living on the Edge (LOTE) study qualitatively explored factors that shape young people's experiences and attitudes towards sexual behaviour and young parenthood in three linked seaside and rural areas in England. It identifies embarrassment as a key risk factor in young people's sexual behaviour and demonstrates why engaging in protective behaviour and seeking information and advice, can be constrained by fear of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
0
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 26 publications
9
56
0
4
Order By: Relevance
“…Da mesma forma, se o produto a ser comprado causa constrangimento, o consumidor pode evitar comprá-lo ou, pelo menos, evitar comprar mais de um tipo de produto constrangedor na mesma ida ao ponto de venda (Bell, 2009). Se a expectativa de uma loja cheia causa essa emoção, o consumidor pode preferir lojas mais vazias, mudando de ponto de venda ou de horário (Brackett, 2004).…”
Section: Situações Para Evitar Experimentar O Constrangimento No Futurounclassified
See 1 more Smart Citation
“…Da mesma forma, se o produto a ser comprado causa constrangimento, o consumidor pode evitar comprá-lo ou, pelo menos, evitar comprar mais de um tipo de produto constrangedor na mesma ida ao ponto de venda (Bell, 2009). Se a expectativa de uma loja cheia causa essa emoção, o consumidor pode preferir lojas mais vazias, mudando de ponto de venda ou de horário (Brackett, 2004).…”
Section: Situações Para Evitar Experimentar O Constrangimento No Futurounclassified
“…Grande parte da literatura sobre constrangimento pode ser dividida em três temas: (a) situações de compra e consumo que antecedem o constrangimento (Blair & Roese, 2013;Brumbaugh & Rosa, 2009;Dahl et al, 2001;Picca & Joos, 2009), (b) situações em que o consumidor age para evitar experimentar esta emoção no futuro (Bell, 2009;Grace, 2007;Miller, 2001) e (c) como o consumidor se comporta no momento em que está constrangido (Brackett, 2004;Ekebas & Arndt, 2015;Picca & Joos, 2009). …”
Section: Introductionunclassified
“…Condom use, for example, can be particularly problematic for young men as it requires that condoms are accessed (usually from feminized spaces including clinics); that their use is negotiated with prospective sexual partners; and it heightens concerns over sexual performance, particularly the loss of erection (Bell, 2009;Coleman & Ingham, 1999;Shai, Jewkes, Nduna, & Dunkle, 2012). The competing masculinity imperatives of sexual voracity and expertise can serve to undermine the pursuit of good sexual health and strategies that appear to be counterintuitive, in this case eschewing condom use, can be effective in performing an approved masculinity.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have suggested that the primary reasons for failure to use condoms ranges from embarrassment at purchase (Bell, 2009;Higuchi & Nakamura, 2010;Moore et al, 2008); a belief that condoms reduce sensitivity and pleasure (Carballo-Diéguez et al, 2011;Crosby, 2005;Randolph, Pinkerton, Bogart, Cecil, & Abramson, 2007); gender and ethnicity (Essien, Ross, Fernandez-Esquer, & Williams, 2005;Figueroa et al, 2005;Kennedy & Roberts, 2009;Lewis, Melton, Succop, & Rosenthal, 2000); lack of condom self-efficacy (Brodbeck, Vilén, Bachmann, Znoj, & Alsaker, 2010;Gillespie-Johnson, 2008;Hoffman et al, 2008 ); and age (Davis, Duncan, Turner, & Young, 2001;Dehne & Riedner, 2005;Flood, 2003;Hulton, Cullen, & Khalokho, 2000;.…”
Section: Condom Use and Other Influences On Safer Sex Behaviormentioning
confidence: 99%
“…The results may be associated with the mature age range in the study, the length of time in a relationship and safer sex behaviors, or its significant correlation with income , since in general, older men have higher incomes. Studies have suggested that the primary reasons for failure to use condoms ranges from embarrassment at purchase (Bell, 2009), a belief that they reduce sensitivity and pleasure (Carballo-Diéguez et al, 2011), age (Davis et al, 2001), and education .…”
Section: Contributions Of Select Demographic Characteristics Masculimentioning
confidence: 99%